"SELECTION OF PARENTAL PAIRS FOR CREATING EARLY-GROWING, HIGH-YIELD AND FIBER-YIELD VARIETIES OF COTTON TYPE G. BARBADENSE.L." (Universal International Scientific Journal, 2026)
In this work, the issues of selecting promising parent forms among samples of the Gossypium barbadense L. species for economically important traits such as early maturity, high yield, and fiber yield were studied. The research was conducted in field conditions, and the main indicators such as growth period, number of cobs, fiber yield, and productivity were analyzed. Based on the results, genetically promising parent pairs for selection were identified and recommendations were developed for creating new varieties.
Keywords: Gossypium barbadense L.; earliness; yield